Fiqh of Fasting Guidance: From Requirements, Pillars, to Nullifiers for the Congregation of Darul Mukhlisin Study Group - Munawaroh, Faridatul; Komariah, Nur; Hartati , Herni (CV. Pustaka An Nur, 2026)
The enthusiasm for observing Ramadan fasting among Indonesian Muslims, including in Indragiri Hilir Regency, is often not accompanied by a comprehensive and contextual understanding of its jurisprudence (fiqh). This potentially diminishes the perfection and even the validity of the worship. The Darul Mukhlisin Study Group in Tembilahan Barat Village, as a community empowerment center, faces similar problems among its congregation, namely: (1) partial and tradition-based knowledge of fasting fiqh, (2) confusion in facing contemporary issues, (3) lack of structured learning resources and interactive delivery methods, and (4) vulnerability to digital misinformation. This community service program aims to: (1) improve a comprehensive understanding of fasting fiqh, (2) equip skills in solving contemporary fiqh problems, (3) enhance religious digital literacy, and (4) strengthen the institutional role of the study group. The method used is Participatory Action Research (PAR), applied in cycles of participatory planning, intervention implementation, observation, and reflection. The core activities consisted of six intensive guidance sessions combining interactive lecture (talqin musytarak), case discussion (hiwar mawdu'i), and simulation (tamtsil al-'amali) methods. Evaluation results showed a 42% increase in conceptual understanding scores. More significantly, a transformation occurred from passive recipients to active learners who were able to analyze fiqh issues by referring to ushul fiqh principles, such as al-masyaqqah tajlibu at-taisir (hardship begets facility). The program also succeeded in building a critical attitude towards religious information on social media. Sustainability was realized through the establishment of a